Lo specchio del mondo - Cambria, Florinda (Mimesis Journal, 2015)
Starting from the Nietzschean thesis on the «spirit of music», the article proposes a reflection about the generative aspects of theatre practice as matrix of all the «dynamic arts». The latter are here understood as the “dramatic” root of every learning experience and, therefore, they reveal, beyond the traditional disciplinary partitions, their original anthropogenetic sense.